Decalcification of Breast Cancer Bone Metastases With EDTA Does Not Affect ER, PR, and HER2 Results. (October 2019) - van Es, Suzanne C.; van der Vegt, Bert; Bensch, Frederike; Gerritse, Sophie; van Helden, Erik J.; Boon, Eline; Angus, Lindsay; Overbosch, Jelle; Menke-van der Houven van Oordt, Catharina W.; Verheul, Henk M.; van Herpen, Carla M.L.; Jager, Agnes; et al.
Abstract : In metastatic breast cancer (MBC), expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER2) guides treatment selection. In case of bone-only metastatic disease, ER, PR, and HER2 status assessment may be hampered by decalcification. We aimed to determine the optimal decalcification method, and to study discordance of receptor expression between paired primary breast tumors and optimally decalcified bone metastases. First, decalcification was simulated using acetic acid, hydrochloric/formic acid, and EDTA on 12 primary breast carcinomas. ER, PR, and HER2 immunohistochemistry (IHC) and HER2 in situ hybridization (ISH) were assessed, before and after the 3 decalcification methods. EDTA was considered the optimal method, as it did not affect IHC and as ISH failed in only 1/16 cases. Hydrochloric/formic acid altered ER and PR results, and, with acetic acid and hydrochloric/formic acid, ISH failed in, respectively, 94% and 100%. Second, ER, PR, and HER2 IHC was performed in paired primary tumors and EDTA-decalcified bone metastases obtained from patients with first presentation of MBC. Clinically relevant discordance was defined as changed receptor status with treatment implications. Paired samples of 77 patients, participating in the IMPACT-MBC trial, were evaluable. Hormonal receptor expression change was clinically relevant in 6 patients (7.9%) and HER2 expression change in 1 patient (1.3%). This study shows that EDTA decalcification minimally affects receptor expression results. The incidence of clinically relevant discordance between the primary tumor and bone metastases is low. These findings support that bone biopsies can reliably be used to assess receptor status.